THE EFFECT OF SQ3R METHOD ON STUDENTS READING COMPREHENSION - Iin Almeina Loebis; Chitra Latiffani (JURNAL PENA EDUKASI, 2019)
Abstract: The population of this research was taken from the grade X . The aim of this study is to discover the effect of applying SQ3R method in reading comprehension. Experimental research design is used as the research method. This research took place at SMA Tamansiswa Kisaran. The population of this research was taken from the grade X of SMA . There were 2 classes, X-1 and X-2 choosen as the sample with 30 students in each class. The classes were divided into two groups namely experimental and control group. The experimental group taught by using SQ3R method and the control group was taught by using conventional method. The instrument used to collect the data was a set of essay tests, which divided as pre test and post test. The result of the research the students who use SQ3R method with a sample of 30 students obtain an average value of 80,66, while the students who use the conventional way with a sample of 30 students obtain an average value of 76,66. So SQ3R method significantly improves the student’s reading comprehension. Keywords: Descriptive text, SQ3R, reading,  Abstrak: Populasi dalam penelitian ini diambil dari siswa kelas X. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penerapan metode SQ3R terhadap pemahaman bacaan. Desain penelitian eksperimental digunakan sebagai metode penelitian. Penelitian ini bertempat di SMA Tamansiswa Kisaran. Populasi penelitian ini diambil dari siswa kelas X SMA. Sampel diambil 2 kelas yaitu X-1 dan X-2 dengan jumlah masing-masing 30 siswa. Kelas dibagi menjadi dua kelompok yaitu kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen diajar dengan metode SQ3R dan kelompok kontrol diajar dengan metode konvensional. Instrumen yang digunakan untuk mengumpulkan data adalah seperangkat tes esai yang dibagi menjadi pre test dan post test. Hasil penelitian siswa yang menggunakan metode SQ3R dengan jumlah sampel 30 siswa memperoleh nilai rata-rata sebesar 80,66, sedangkan siswa yang menggunakan cara konvensional dengan jumlah sampel 30 siswa memperoleh nilai rata-rata 76,66. Jadi metode SQ3R secara signifikan meningkatkan pemahaman bacaan siswa. Kata Kunci : Teks deskriptif, SQ3R, Membaca.